2019
DOI: 10.1186/s12967-019-2024-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel CD147 inhibitor, SP-8356, reduces neointimal hyperplasia and arterial stiffness in a rat model of partial carotid artery ligation

Abstract: Background Neointimal hyperplasia and its related arterial stiffness are the crucial pathophysiological features in atherosclerosis and in-stent restenosis. Cluster of differentiation 147 (CD147), a member of the immunoglobulin super family that induces the expression of matrix metalloproteinase-9 (MMP-9) by dimerization, may play important roles in neointimal hyperplasia and may therefore be an effective target for the treatment of this condition. Here, we investigated whether a novel CD147 inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…CD147 homophilic interactions, such as dimerization and CD147-CypA interactions, are the two dominant mechanisms leading to MMP-9 upregulation [16]. Accumulated evidence from our previous [20] and current studies suggests that SP-8356 can synergistically inhibit MMP-9 activity by binding to CD147 and simultaneously attenuating CD147 dimerization and CD147-CypA interactions. However, detailed basic mechanisms require further investigation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…CD147 homophilic interactions, such as dimerization and CD147-CypA interactions, are the two dominant mechanisms leading to MMP-9 upregulation [16]. Accumulated evidence from our previous [20] and current studies suggests that SP-8356 can synergistically inhibit MMP-9 activity by binding to CD147 and simultaneously attenuating CD147 dimerization and CD147-CypA interactions. However, detailed basic mechanisms require further investigation.…”
Section: Discussionmentioning
confidence: 59%
“…SP-8356((1S,5R)-4-(3,4-dihydroxy-5-methoxystyryl)-6,6-dimethylbicyclo[3.1.1]hept-3-en-2-one), a novel synthetic small-molecule drug, is a (1S)-(−)-verbenone derivative with anti-inflammatory and anti-oxidative activities ( Figure 1A) [19]. In addition, we recently found that SP-8356 binds to CD147 and reduces neointimal hyperplasia through inhibition of MMP-9 activity [20]. We also found that SP-8356 has an anti-tumor effect through inhibition of CD147/MMP-9 pathway [21].…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism is that CD147 can serve as both receptor and ligand for adjacent CD147, which is called the homophilic interaction such as dimerization [13,31,32]. Recently, we found that SP-8356 shows a high binding affinity with CD147 and directly inhibits CD147 dimerization [14]. Thus, the inhibitory effect of SP-8356 on CD147 dimerization may contribute to its anti-fibrotic effect in the alkali-burned cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that a novel synthetic small-molecule drug SP-8356 ((1S,5R)-4-(3,4-dihydroxy-5-methoxystyryl)-6,6-dimethylbicyclo[3.1.1] hept-3-en-2-one) directly binds to CD147 thereby inhibiting neointimal hyperplasia and stabilizing plaque vulnerability in animal models through the inhibition of MMP-9 activity [14,15] . Furthermore, we also found that SP-8356 possesses anti-tumor effect through the inhibition of CD147/MMP-9 pathway [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BSG inhibitors are now being developed and tested [66][67][68], and we hope our study can provide some evidence for BSG targeted treatment of TC.…”
Section: Discussionmentioning
confidence: 99%